Defining dialogues: tracing the evolution of human-machine communication - Prahl, Andrew (2024)
This introduction to the volume discusses the evolving field of Human-Machine Communication (HMC), drawing on insights from the philosophy of science. We explore critical debates in the field, underscoring the importance of challenging assumptions, embracing interfield work, and fostering dialogue in shaping our understanding of HMC. Moreover, we celebrate the vibrant collaboration between disciplines that drives progress in HMC. This piece serves as an invitation to join the exploration of this collection and contribute to shaping the future of HMC.